Strategic Mandate: A Systematic Review on the Role of Institution in Enhancing Educator and Student Advanced Digital Skills for AI-Driven Entrepreneurial Readiness in Indonesia Entrepreneurship Education - Tahani Badrul Munir; Ummi Salwa Ahmad Bustamam; Suhaida Herni Suffarruddin (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by (Tier 2)